Increased expression of BDNF transcript with exon VI in hippocampi of patients with pharmaco-resistant temporal lobe epilepsy. (9th February 2016) - Martínez-Levy, G.A.; Rocha, L.; Lubin, F.D.; Alonso-Vanegas, M.A.; Nani, A.; Buentello-García, R.M.; Pérez-Molina, R.; Briones-Velasco, M.; Recillas-Targa, F.; Pérez-Molina, A.; San-Juan, D.; Cienfuegos, J.; et al.
Highlights: BDNF exon VI was up-regulated in the hippocampus of TLE patients. Expression of BDNFVI was related to the use of Topiramate or Sertraline. Methylation levels at BDNF promoter VI were not associated to these effects. Abstract: A putative role of the brain-derived neurotrophic factor (BDNF) in epilepsy has emerged from in vitro and animal models, but few studies have analyzed human samples. We assessed the BDNF expression of transcripts with exons I (BDNFI), II (BDNFII), IV (BDNFIV) and VI (BDNFVI) and methylation levels of promoters 4 and 6 in the hippocampi of patients with pharmaco-resistant temporal lobe epilepsy (TLE) ( n = 24). Hippocampal sclerosis (HS) and pre-surgical pharmacological treatment were considered as clinical independent variables. A statistical significant increase for the BDNFVI ( p < 0.05) was observed in TLE patients compared to the autopsy control group ( n = 8). BDNFVI was also increased in anxiety/depression TLE ( N = 4) when compared to autopsies or to the remaining group of patients ( p < 0.05). In contrast, the use of the antiepileptic drug Topiramate (TPM) ( N = 3) was associated to a decrease in BDNFVI expression ( p < 0.05) when compared to the remaining group of patients. Methylation levels at the BDNF promoters 4 and 6 were similar between TLE and autopsies and in relation to the use of either Sertraline (SRT) or TPM. These results suggest an up-regulated expression of a specific BDNF transcript in patients with TLE, an effect that seems to be dependent on the use of specific drugs.